Faktor Yang Berhubungan Dengan Rendahnya Minat Wanita Usia Subur Dalam Penggunaan KB Intrauterine Device - Putri, Yuwari Natalia; Lathifah, Nur; Hidayah, Nur (Pusat Riset dan Inovasi Nasional, 2023)
Family planning is a government program to limit the birth rate. One of them is the use of effective contraceptives Intra Uterine Device (IUD), but in general in Central Kalimantan the demand for contraceptives is very low, especially in the working area of the Timpah Health Center. The purpose of the study was to analyze factors associated with the low interest of women of childbearing age in the use of Intra Uterine Device contraceptives at UPT Puskesmas Timpah. The method used is quantitative research with a cross sectional design. The data collection instrument uses questionnaires taken with Total Sampling techniques. The respondents were women of childbearing age. The results of the study of women of childbearing age on IUD birth control were obtained by 11 respondents having moderate interest (55%), knowledge level less than 23 respondents (57.5%), low parity < 2 children as many as 30 people (75%), elementary / junior high school graduate education 24 people (60%), husbands did not support 28 people (70%). The results of the chi-square test on Fisher Exact p-value obtained knowledge with interest p = 0.432, parity with interest p = 1,000, education with interest p = 0.407, husband support with interest p = 1,000.